2013
DOI: 10.1088/0029-5515/53/9/093007
|View full text |Cite
|
Sign up to set email alerts
|

Impact and mitigation of disruptions with the ITER-like wall in JET

Abstract: Abstract:Disruptions are a critical issue for ITER because of the high thermal and magnetic energies that are released on short time scales, which results in extreme forces and heat loads. The choice of material of the plasma facing components (PFCs) can have significant impact on the loads that arise during a disruption. With the ITER-like wall (ILW) in JET made of beryllium in the main chamber and tungsten in the divertor, the main finding is a low fraction of radiation. This has dropped significantly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 22 publications
4
125
0
Order By: Relevance
“…is likely due to the fact that the fastest IDDB current quenches occur in DIII-D, which has entirely carbon plasma facing components (PFC) that are known to emit significant amounts of carbon impurity into the plasma during the thermal quench (TQ) [47]. The distribution for natural disruptions skews significantly towards longer € Δt cq for beryllium first wall and tungsten divertor devices, as has recently been reported for the ITER-like wall in JET [51] (data not presently available in IDDB) , and is expected to do so in ITER as well.…”
mentioning
confidence: 85%
“…is likely due to the fact that the fastest IDDB current quenches occur in DIII-D, which has entirely carbon plasma facing components (PFC) that are known to emit significant amounts of carbon impurity into the plasma during the thermal quench (TQ) [47]. The distribution for natural disruptions skews significantly towards longer € Δt cq for beryllium first wall and tungsten divertor devices, as has recently been reported for the ITER-like wall in JET [51] (data not presently available in IDDB) , and is expected to do so in ITER as well.…”
mentioning
confidence: 85%
“…The dynamics of the unmitigated disruptions with the ILW is found to be different with respect to the C-wall [7]. In this context, it was found that mitigation by Massive Gas Injection became a necessity for ILW operations at plasma currents higher than 2.0 MA [8].…”
Section: Jet-past and Expected Performancementioning
confidence: 96%
“…Successful disruption mitigation [46][47][48] with massive gas injection of a mixture of argon and deuterium has been obtained and is now mandatory for JET operation above 2 MA. The radiation efficiency of massive gas injection using the disruption mitigation valve (DMV) on JET (using a mixture of 90%D 2 +10%Ar) is 90% at a low thermal energy fraction W th /W mag of < 0.3 (where W th is the thermal energy and W mag is the magnetic stored energy), and reduces to 70% radiation efficiency at W th /W mag ∼ 0.5.…”
Section: Disruptions and The Generation Of Resmentioning
confidence: 99%